PEMANFAATAN LIMBAH PELEPAH SAWIT SEBAGAI PAKAN TERNAK SAPI PADA KELOMPOK PEMUDA TANI TUNAS MUDA - Nurhaita Nurhaita; Neli Definiati; Suliasih Suliasih (Universitas Bengkulu, 2018)
The prevalent problem of partnership is the difficulty of supplying green feed. Palm oil frond was the most available palm oil waste for feed utilization by partnership because both partners were located in palm oil plantation area. For optimum feed utilization, palm oil frond was to undergo particular process through ammoniation with urea and fermentation with MOL (local microorganism) from cow manure. The objective of this activity was to introduce the processing technology of palm oil frond by ammoniation and fermentation in partner groups. The variables of this activity were palm oil frond ammoniation, fermented palm oil frond, and mol from cow manure. This social service activity was conducted by extension method, training and demonstration, as well as group supervision and partnership. The result of this event demonstrated that partner groups were able and skillful in processing palm oil frond through ammoniation and fermentation, as well as creating MOL from cow feces as fermentation starter. Ammoniation palm oil was characterized by ammoniac smell and intact green texture. Good quality fermented palm oil frond was tapai- like fragrant, moldless and mucus-free yellowish green. Ammoniation and fermented palm oil frond had good palatability as observed from the response of cow’s immediate intake on the first administration without necessarily long adaptation. Conclusion: Processing technology of palm oil frond was well accepted and applicable in partner groups as solution to green feed problem. Keywords: ammoniation, fermentation, mol cow manure, palm oil frond, cattle feed